Presentation of a transhumant sheep management farm in Szeklerland - Bodnár, Ákos; Bereczki, Szabolcs; Póti, Péter; Egerszegi, István; Pajor, Ferenc (Animal welfare, Ethology and Housing Systems (AWETH), 2021)
In our work we present some elements and farming possibilities of the sheep sector of Szeklerland, which has developed over several centuries. For that, the available literature, personal interviews with local sheep farmers, and an outstanding extensive sheep farm have been presented. This farm has been awarded several times in the "Harghita County Model" program. In this study, we evaluated the structure, the genetic background of the livestock, the production data, and the economic results of the sheep farm in two farming years. As a result of our research, we have found that with enthusiastic and persistent work for farmers and technological development that adapts to the circumstances, many exploitable opportunities open up in traditional, extensive sheep farming. The herd produced average production values for the given breeds. Over the centuries, the different varieties of the Tsigai breed developed here have adapted to the transhumant animal keeping and to the often-harsh climatic conditions and forage supply.
Keywords: grazing; Transylvania; Tsigai breed; tradition